15 Assessing the challenges in nurse staffing and nurse management within the NHS, and formulating a strategy to address them. (12th November 2018) - Razak, Ali Abdall; Abdullah, Shahbaz; Illa, Eduardo de Arede-Simoes; Jennings, Thomas; Light, Emily; Martinuzzi, Michela; Tourmouzis, Konstantinos
Abstract : Introduction: Leaders in nurse staffing face many challenges in the modern National Health Service (NHS). With political unrest due to the Brexit vote, financial instability, and insufficient recruitment levels, managers of nursing have much to consider in long term NHS strategy. Aims: To assess the managerial challenges with the objective of prioritising them to help develop a strategy. To determine the front-line opinions regarding Brexit's effect on nursing leadership decisions. Methods: Qualitative Study. Expert interviews were conducted with nurses from Band 6 to Directors of Nursing within a large London-based Trust. Transcripts of the interviews were analysed for themes, and strategies were suggested accordingly. Results: The main challenges facing management are poor leadership training for nurses transitioning to higher bands, avoiding high turnover rates within a Trust, and domestic recruitment to the career. There was unanimous agreement (11 interviews) that Brexit was a non-factor in long-term strategy. European Union (EU) nurse retention was low. This was attributed to the introduction of the International English Language Testing System (IELTS) in 2016, and their overall short-term career goals within the UK. Thus, recruitment efforts had already shifted to the Asian subcontinent. Conclusion: Strategies should focus on leadership training, lowering turnover rates, and domestic recruitment. As such, the development of formal leadership programmes specific to nurses will be crucial in training cost-aware, and proficient leaders. An advice package to Trusts collating successful retention methods will empower managers to quickly uptake strategies. Career campaigns are recommended to improve local recruitment. Throughout, the long-term nurse management strategy should not lend itself too heavily to Brexit.